2021
DOI: 10.1136/bmj.n2061
|View full text |Cite
|
Sign up to set email alerts
|

A new framework for developing and evaluating complex interventions: update of Medical Research Council guidance

Abstract: The UK Medical Research Council’s widely used guidance for developing and evaluating complex interventions has been replaced by a new framework, commissioned jointly by the Medical Research Council and the National Institute for Health Research, which takes account of recent developments in theory and methods and the need to maximise the efficiency, use, and impact of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
2,447
0
53

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,634 publications
(2,968 citation statements)
references
References 73 publications
16
2,447
0
53
Order By: Relevance
“…In this study informal caregivers were found to generally be very satisfied with the ICBT intervention which indicates its potential for this population. (21). There is also a set of common core elements outlined, relevant for all phases: consideration of the context, refinement of the theory, engagement of stakeholders, identification of uncertainties, refinement of the intervention and consideration of the economic factors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study informal caregivers were found to generally be very satisfied with the ICBT intervention which indicates its potential for this population. (21). There is also a set of common core elements outlined, relevant for all phases: consideration of the context, refinement of the theory, engagement of stakeholders, identification of uncertainties, refinement of the intervention and consideration of the economic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Various frameworks exist for guiding the development, evaluation, and implementation of the internet interventions. The Medical Research Council (MRC) framework for complex interventions (interventions including several interacting components among other characteristics) ( 19 21 ) is a well-known and cited framework. It suggests that the intervention research consists of four phases: identification or development of an intervention, feasibility, evaluation, and implementation ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the acceptability of behaviour change interventions is overlooked, their effectiveness may be undermined [12]. Acceptability of health behaviour interventions has generally been conceptualised as the level of tolerance required to undertake health interventions or, more recently, the perceived appropriateness to those delivering or receiving a healthcare intervention based on their cognitive and emotional responses [13].…”
Section: Introductionmentioning
confidence: 99%